ANALISIS KESESUAIAN KUALITAS AIR KOLAM BERDASARKAN PARAMETER pH, DO, AMONIAK, KARBONDIOKSIDA DAN ALKALINITAS DI BALAI BENIH DAN INDUK IKAN AIR TAWAR (BBI-IAT) KECAMATAN KARANG INTAN KABUPATEN BANJAR - Fidia Ningsih; Mijani Rahman; Abdur Rahman (Fish Scientiae, 2019)
In this research data obtained from measurements or observations a represented in the form of tabulated and graphics so clear the existence of variation search on each point of observation. Data analysis using STORET model and EQI. Statistical tests performed on 6 variables (Kolam1, II, III, IV, Indoor Pool, Outdoor Pool V, VI). Each variable water quality analysis: pH, DO, NH3, CO2 and Alkalinityas much as 6 times the observation (Sunday I, II and III of the Week Week) on the morning and afternoon. To know the influence of parameters (pH, DO, NH3, CO2 and Alkalinity) of raw water quality pond done Multiple Linear regression analysis. Linear regression analysis of multiple shown r of ( 0,751 ), it means that happened a positive relationship between variables y (dependent variable) and x (independent ). R2 / determinan of ( 0,564 ), it means of 56,4 % quality standards apool water affected by water quality swimming ( pH, DO, NH3, of CO2 alkalinity )and of 43,6 % affected by another variable. Of a result of calculation to research obtained equation y = 0,484 - 0,067x1 - 0,027x2 - 0,506x3 - 0,036x4 0,002x5 -, it means any additional value the constant ( a ) by 0,484. Its influence will resulting in a decline of water quality is at ph ( X1 ) by 0,067, do ( X2 ) by 0,027 NH3 ( X3 ) by 0,506,CO2 ( X4 ) by 0,036 mg / l and alkalinity ( X5 ) by 0,002 mg / l.